2019
DOI: 10.5507/ag.2019.013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aerobics on weight and fat mass loss in adult women: Systematic review and meta-analysis

Abstract: PA is used as a means of intervention especially because a number of prospective studies confirm its protective effect on adiposity (Fogelholm & Kukkonen-Harjula, 2000; Kay & Fiatarone Singh, 2006). However, PA intervention should reflect the current health condition and degree of obesity (Ball, Owen, Salmon, Bauman, & Gore, 2001; Petersen, Schnohr, & Sorensen, 2004). The result of the intervention is influenced by a number of factors such as its duration. This modifiable factor affects not only the effectiven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…improve eustress and blood glucose control in type 2 diabetes mellitus (Amir et al, 2021), reduce body weight (Hiklova & Gába, 2019), improve the haematological profile (Harianja & Garini, 2021) and relieve non-specific neck pain (Paraskevopoulos et al, 2023) as well as various other health benefits. As long as aerobics is done correctly and the intensity is maintained, various healthy and fit benefits can be felt.…”
Section: Research Resultsmentioning
confidence: 99%
“…improve eustress and blood glucose control in type 2 diabetes mellitus (Amir et al, 2021), reduce body weight (Hiklova & Gába, 2019), improve the haematological profile (Harianja & Garini, 2021) and relieve non-specific neck pain (Paraskevopoulos et al, 2023) as well as various other health benefits. As long as aerobics is done correctly and the intensity is maintained, various healthy and fit benefits can be felt.…”
Section: Research Resultsmentioning
confidence: 99%
“…Závažnosť postihnutia bola determinovaná prostredníctvom škály EDSS (Kurtzke, 1983) (Hiklová, 2019). Rezistovaný tréning pomáha zvyšovať nárast Pri hodnotení rýchlosti chôdze prostredníctvom 10 mWT sa za minimálnu klinicky významnú zmenu pre pacientov s RS (EDSS 3-6) považuje zníženie rýchlosti o 23% alebo zvýšenie rýchlosti o 30 % (Nilsagard, 2007).…”
Section: Výsledkyunclassified
“…added a high-intensity exercise with high energy expenditure for 12-week are more effective in reducing the body weight, body fat, waist circumference, and waist to hip ratio, whereas a low-intensity exercise reduce body weight and body fat significantly. On the other hand some studies identified that an aerobic exercise programme can reduce fatty tissue as well but the type of Aerobic Exercise and the duration of the intervention should be considered (Janssen et al, 2002;Hiklová, and Gába, 2019…”
mentioning
confidence: 99%